Arsenic sorption and oxidation by natural manganese-oxide-enriched soils: Reaction kinetics respond to varying environmental conditions - Matthew H.H. Fischel; Catherine E. Clarke; Donald L. Sparks (Geoderma, 2024)
Manganese-oxides are some of the strongest oxidants and sorbents in the environment, which impact many geochemical processes. However, nearly all our understanding of manganese-oxides’ reaction kinetics is based on laboratory-synthesized minerals. This study quantifies the oxidative kinetics and adsorptive capacity of five soils rich in pedogenic manganese- and iron-oxides through arsenite oxidation batch reactions over a range of pHs and temperatures to mimic diverse environmental conditions. The two A horizons were less reactive and enriched in manganese(IV), compared to the B horizons, particularly the subsoil containing the manganese-rich wad material. The reaction kinetics fit a pseudo-first-order reaction with distinct fast and slow phases. The baseline reactions were pH 7.2 at 23 °C. Adjusting pH to 4.5 or 9.0 increased the reaction rates. Decreasing the temperature to 4.0 °C reduced the reaction kinetics, while raising the temperature to 40 °C increased the arsenite oxidation rate. pH and temperature changes alter the reaction kinetics due to shifts related to the point of zero charge, the total system energy, and surface passivation from adsorbing arsenic and manganese species. Synchrotron X-ray fluorescence mapping indicates arsenic only penetrates the surficial layers of most manganese-oxide-containing nodules found in the soil. After the arsenite oxidation reaction in the pedogenically weathered subsoil, X-ray absorption spectroscopy demonstrates significant differences in the average manganese oxidation number between the nodules’ outer layers compared to the soil matrix and nodule centers. The kinetic and sorption parameters give critical insight into determining the mobility and species of arsenic and other redox-sensitive contaminants in manganese-containing environmental systems over appropriate timescales.